Effectitions as a new instrument in sustainable development policy - the conceptual approach = Efektycje jako nowy instrument w polityce zrównoważonego rozwoju - ujęcie koncepcyjne - Ziółkowski, Bożydar (Zielona Góra: Faculty of Economics and Management Press)
Effective dissemination of sustainable development is possible when the instruments for its implementation are continuously improved. The concept of effectitions is an example of such an approach. It extracts from the group of innovations for sustainable development, such technologies which have no negative environmental impacts. The presented paper presents the nature of effectitions in the context of eco-innovations and sustainable development policy.
Keywords: efektycje; ekoinnowacje; zrównoważony rozwój; ochrona środowiska; effectitions; eco-innovations; sustainable development; environment protection